The wage effects of employers' associations: A case study of the private schools sector - Pedro S. Martins (Global Labor Organization (GLO), 2022)
Does employers' association (EA) membership affect the wages paid by firms? Such effects could follow from several channels, including increased productivity, different management practices, or employer collusion promoted by EA affiliation. We test these hypotheses drawing on detailed matched employer-employee panel data, including timevarying EA affiliation and worker mobility across firms. We consider the case of private schools in Portugal, 2010-2020, and its EA, and develop a methodology to delimit the sector's scope. We find that, even when controlling extensively for worker characteristics, including worker fixed effects, EA firms pay significantly higher wages. However, when controlling for firm fixed effects, these wage differences are significantly reduced or disappear. Our evidence indicates that the EA wage premium can be largely explained by the selection of high-wage firms (but not high-wage workers) into EA membership.
Keywords: J53; J62; L40; 330; Employers organisations; Worker mobility; Social dialogue